Impact of globalization on the environment in major CO2-emitting countries: Evidence using bootstrap ARDL with a Fourier function - Wu, Cheng-Feng; Chang, Tsangyao; Wu, Tsung-Pao; Leng, Kai-jun; Lin, Meng-Chen; Huang, Shian-Chang (Frontiers in Public Health, 2022)
Alongside sustainable development as a major global issue in recent decades, the contribution made by globalization to environmental issues has also become crucial. Prior studies have focused on how trade in globalization influences the environment. However, multiple structures including economic, social, and political factors are important in globalization, the integration of which needs to be considered in sustainable development. Sharp and smooth breaks time series models are the consequence of structures in the real world. Thus, the present study reexamined the nexus between globalization and the environment in China, the United States, and India using the bootstrap autoregressive-distributed lag test with a Fourier function. The empirical results indicate that the nexus between globalization and the environment is cointegrated for a long-term association in the United States. With respect to the short term, globalization is improving the environment in the United States and India. However, in China, globalization is resulting in environmental degradation. This research will assist policymakers in developing comprehensive strategies for sustainable development.